2003
DOI: 10.1142/s0218625x03005414
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning by Wettability Control of the SiO2 Surface with Ultraviolet Irradiation

Abstract: A new phenomenon has been described for fabrication micropatterning by changing SiO2 surface wettability with ultraviolet irradiation. The most possible reason is the elimination of surface oxygen vacancies at bridging sites. With this technique reconstructed, it may be applicable to assembly of microelectronic circuits in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…19(d)] Light can drive droplet motion when the surface is coated with a photosensitive material. Static optowetting, i.e., a change in contact angle change due to uniform light irradiation, has been reported ͑Wang et al, 1997; Abbott et al, 1999;Shin and Abbott, 1999;Miyauchi et al, 2002;Huang et al, 2003͒. Furthermore, droplet motion has been driven using gradients in light intensity ͑Ichimura et Oh et al, 2002͒.…”
Section: B Surfaces With Wettability Gradientsmentioning
confidence: 99%
“…19(d)] Light can drive droplet motion when the surface is coated with a photosensitive material. Static optowetting, i.e., a change in contact angle change due to uniform light irradiation, has been reported ͑Wang et al, 1997; Abbott et al, 1999;Shin and Abbott, 1999;Miyauchi et al, 2002;Huang et al, 2003͒. Furthermore, droplet motion has been driven using gradients in light intensity ͑Ichimura et Oh et al, 2002͒.…”
Section: B Surfaces With Wettability Gradientsmentioning
confidence: 99%
“…As the surface area to volume ratio scales to the inverse of the device dimension, surface effects happen to be very prominent in microfluidics-based systems (Lee et al 2002;Huang et al 2003;Gascoyne & Vykoukal 2004;Madou 2002). This has been typically explored in the generation of controlled monodisperse microdroplet between two immiscible fluids (Thorsen et al 2001) and the radius of the droplet has been shown scale as the inverse of Capillary number.…”
Section: Developing Surface Effectsmentioning
confidence: 99%